Manajemen Komunikasi Pemasaran Fatahillah Ginting Photography Dalam Mempertahankan Eksistensi di Masa Pandemi Covid-19 - Nursidiq Bagas Saputra; Fadhil Pahlevi Hidayat (Universitas Muhammadiyah Sumatera Utara, 2022)
Photography businesses in general have their own management in managing, maintaining and developing their business so that they still exist and are known by the general public. By carrying out various marketing management, ranging from social media to print media with the aim of attracting as many people as possible so that the photography service business can continue to exist and develop. As done by Fatahillah Ginting Photography. This study aims to find out the marketing management applied by Fatahillah Ginting Photography to maintain the existence of its photography business in the face of the Covid-19 pandemic and to find out what obstacles Fatahillah Ginting Photography faced during the Covid-19 pandemic. This study uses the theory of marketing communication mix with a particular view of advertising (advertising) and Public Relations (public relations). This research uses a qualitative descriptive research method with data collection methods through in-depth interviews, documentation and observation. Informants in this study were the founder, owner, brand communication, account executive and marketing of fatahillah ginting photography. The results of the research that have been carried out, Fatahillah ginting photography marketing communication management in maintaining existence during the covid-19 pandemic on marketing communication elements where the outline consists of advertising through Instagram, Youtube and Neon Box and public relations (public relations) carried out by the founder, owner, brand communication, account executive, marketing and all employees of fatahillah ginting photography. As for the obstacles faced by Fatahillah Ginting Photography in maintaining its existence during the Covid-19 pandemic, namely the large-scale social restrictions (PSBB) that took place in the city of Medan and in other cities so that there were no big events, is it weddings or non-weddings which took place at the time. The covid-19 pandemic is ongoing.